2018
DOI: 10.1002/jcp.26938
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in alcoholic liver disease: Recent advances and future applications

Abstract: Alcoholic liver disease (ALD) is characterized by hepatocyte damage, inflammatory cell activation, and increased intestinal permeability leading to the clinical manifestations of alcoholic hepatitis. Selected members of the family of microRNAs (miRNAs) are affected by alcohol, resulting in an abnormal miRNA profile in the liver and circulation in ALD. Increasing evidence suggests that miRNAs that regulate inflammation, lipid metabolism and promote cancer are affected by excessive alcohol administration in mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 55 publications
(106 reference statements)
1
18
0
Order By: Relevance
“…The liver is the main organ responsible for metabolizing ethanol, and thus it has been considered for a long time a major organ damaged by the harmful use of alcohol[ 36 ]. The expression of a wide variety of miRNAs is potentially regulated by many factors, such as alcohol, diet, cigarette smoking, and other drugs[ 37 ]. To date, there has only been one previous study focusing on the role of alcohol-regulated miRNAs in HCC pathogenesis and progression.…”
Section: Discussionmentioning
confidence: 99%
“…The liver is the main organ responsible for metabolizing ethanol, and thus it has been considered for a long time a major organ damaged by the harmful use of alcohol[ 36 ]. The expression of a wide variety of miRNAs is potentially regulated by many factors, such as alcohol, diet, cigarette smoking, and other drugs[ 37 ]. To date, there has only been one previous study focusing on the role of alcohol-regulated miRNAs in HCC pathogenesis and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Liver is the main organ responsible for metabolizing ethanol, and thus it has been considered for a long time a major organ damaged by the harmful use of alcohol [34]. The expression of a wide variety of miRNAs is potentially regulated by many factors, such as alcohol, but also diet, cigarette smoking, and other drugs [35]. To date, there has only been one previous study focusing on the role of alcohol-regulated miRNAs in HCC pathogenesis and progression.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs’ dysregulation has been shown to have high prognostic and predictive value in a broad spectrum of liver diseases, including viral hepatitis, ALD and NAFLD, fibrosis, and HCC [109]. miRNAs are also stable in the circulation (blood, urine) thus representing potential biomarkers for ALD [110,111]. Several studies have shown that miRNAs expression could be altered by alcohol consumption [112,113,114].…”
Section: Epigenetic Factors Involved In Ald Pathogenesismentioning
confidence: 99%
“…Specifically, it regulates macrophages polarization and inflammasome activation and it was found to be elevated in serum and in neutrophils of both alcoholics and ethanol-fed mice. However, human neutrophil expression of miR-223 remains still controversial and it could be the result of different exposure time to alcohol [111]. miR-223 deficient mice display a more pronounced hepatic neutrophil infiltration and more severe liver damage by favoring IL6 and phagocytic oxidase (phox) p47phox expressions and oxidative stress [137].…”
Section: Epigenetic Factors Involved In Ald Pathogenesismentioning
confidence: 99%